Low-density Lipoproteins and Degrees of Cardiovascular Risk in Adults over 40 Years of Age: Case-control Study - Abel Pérez Pavón; Francisco Sánchez Hernández; Karla Doriam Gámez Ávalos; Donovan Casas Patiño; Alejandra Rodríguez Torres (Revista Finlay)
Foundation: cardiovascular diseases are the main cause of death and disability in the world. Its incidence and prevalence has increased over the last decade and accounts for a third of all deaths. Objective: determine the association of LDL-C and degrees of cardiovascular risk in adults over 40 years of age in the Family Medicine Unit #43 of the Mexican Social Security Institute. Method: an investigation was carried out with a case-control design during 2023, using the 1:1 case-control ratio formula, (230 subjects) who met the selection criteria. Information collection was carried out through an Excel database, the contrast of variables was carried out with the X2 formula. Using the SPSS version 25 Windows program. Results: the female gender was the most frequent, the average age was 62 years, elevated total cholesterol presented 109 (94.8) patients with high cardiovascular risk, an MRI was calculated: 43,279, CI: 95 %, ( 17,347-107,980), LDL cholesterol presented 68 % (59.1) with cardiovascular risk and an MRI: 1.28, CI: 95 % (0.760-2.158), the evaluation of triglycerides with high figures presented 50.4 % (58), OR: 0.037, 95 % CI (0.013-0.106). Conclusions: the average age of the subjects was 62 years, the female sex predominated, with a greater proportion of married people, the level of schooling that predominated was high school, the catholic religion was more frequent and the subjects were from the urban area. Lipid variables such as total cholesterol and LDL-C presented statistical significance in relation to cardiovascular risk.